2020
DOI: 10.1109/access.2020.2998531
|View full text |Cite
|
Sign up to set email alerts
|

Robust Finite-Time Stabilization for Uncertain Discrete-Time Linear Singular Systems

Abstract: This paper considers the robust finite-time stabilization problem for a class of discrete-time linear singular systems with norm-bounded parameter uncertainties. With the introduction of an additional matrix to describe the algebraic relationship between the slow subsystem and fast subsystem of a discretetime linear singular system, a matrix inequality condition is first given for a discrete-time linear singular system to be regular, causal and finite-time stable. With this condition, the robust finite-time st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…2. In contrast to the works [17][18][19] about finite-time stability analysis of singular single systems, this paper attempts to tackle the finite-time stability issue of singular multi-agent systems by considering input time-varying delay, Lipschitz non-linear dynamics and controller gain perturbation at the same time. Therefore, this paper is closer to the practical engineering systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2. In contrast to the works [17][18][19] about finite-time stability analysis of singular single systems, this paper attempts to tackle the finite-time stability issue of singular multi-agent systems by considering input time-varying delay, Lipschitz non-linear dynamics and controller gain perturbation at the same time. Therefore, this paper is closer to the practical engineering systems.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, references [10–12] assume that the controller gain keeps constant in the actual process, which is unreasonable and unrealistic. On the contrary, this paper considers that inaccuracy exists in the execution of the controller and designs a non‐fragile distribute controller to solve the problem. In contrast to the works [17–19] about finite‐time stability analysis of singular single systems, this paper attempts to tackle the finite‐time stability issue of singular multi‐agent systems by considering input time‐varying delay, Lipschitz non‐linear dynamics and controller gain perturbation at the same time. Therefore, this paper is closer to the practical engineering systems.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the finite-time transient performance should be considered. Recently, finite-time stability and H ∞ control problems have gradually become a well-researched topic and have been applied to many systems [15][16][17][18] . In 2020, Wang J X et al [15] considered the problem of robust finite-time stabilization for uncertain discrete-time linear singular systems.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, finite-time stability and H ∞ control problems have gradually become a well-researched topic and have been applied to many systems [15][16][17][18] . In 2020, Wang J X et al [15] considered the problem of robust finite-time stabilization for uncertain discrete-time linear singular systems. Feng T et al [16] studied the problem of finite time stability and stabilization for fractional-order switched singular continuous-time system.…”
Section: Introductionmentioning
confidence: 99%
“…The descriptor system [1]- [3], also known as singular system, has provided a unified and useful modeling method for many real applications, such as electricity, aerospace, and social economy. Therefore, it is clearly observed that the study on descriptor system is active over the recent decades and has made great process [4], [5], in which, as the most important field, the problem of asymptotic stability and feedback stabilization have been attracted more attention from researchers. And some results involving the research on system performance analysis for descriptor system have been reported, for instance, in [6], the problem of a reduced-order H ∞ controller based on the geometric structures was solved.…”
Section: Introductionmentioning
confidence: 99%